Assessment of the necessity of uterine artery embolization during suction and curettage for caesarean scar pregnancy: a prospective cohort study - Jie Ou; Ping Peng; Chunying Li; Lirong Teng; Xinyan Liu (BMC, 2020)
Abstract Background Uterine artery embolization (UAE) followed by suction and curettage is a common conservative treatment for caesarean scar pregnancy (CSP), but the advantages of suction and curettage alone are underestimated due to the lack of standards for selecting appropriate cases for which this approach would be applicable. We sought to identify indicators with which to assess the need for UAE during suction and curettage. Methods The prospective cohort consisted of 105 women diagnosed with CSP in Peking Union Medical College Hospital between January 2016 and September 2018 who were followed up until 60 days after surgery. The main outcome was the therapy used, and secondary outcomes included recovery, bleeding, surgery time, length of hospital stay, and total cost. Results We found that β-human chorionic gonadotropin (β-hCG) levels were significantly lower (P < 0.05), foetal cardiac activity was significantly lower (P < 0.05), the myometrial layer was significantly thicker (P < 0.05), expenditures were lower and lengths of hospital stay were shorter in patients who received suction and curettage alone (the non-UAE group) than in those who received UAE followed by suction and curettage (the UAE+ group). In addition, for CSP patients, UAE might be less necessary when the myometrial thickness is ≥2 mm and the gestational sacmeasures ≤5 cm, and suction and curettage alone may be safer for these patients. Conclusion Suction and curettage alone is a more suitable option than UAE followed by suction and curettage because the former carries a lower cost, shorter length of hospital stay, and lower risk of adverse events. Regarding risk factors, patients with a lower uterine segment thickness ≥ 2 mm and a gestational mass diameter ≤ 5 cm have an increased probability of being successfully treated with suction and curettage alone.